SYMBOLE IGRZYSK OLIMPIJSKICH Z PERSPEKTYWY LINGWISTYKI DYSKURSU - Loewe, Iwona (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The author recognizes the mascot, the name of the mascot and the logo as the eponymous symbols of the Olympic Games. She is aware that the subject is more extensive and also contains the website of the International Olympic Committee (IOC), the IOC logo, the IOC advertising spot and slogan, the Olympic hymn and flag, the motto of Baron de Coubertaine, the Olympic torch, the song of the Games since 2002 and the webpage of the following games. With respect to this division the author assumes that the analysed symbols should show global trends, giving proof of the universality of the event and local trends providing evidence of a connection to a specific host country. These trends are subject to observations at the level of sign, meaning, value and discourse. As a result of the interpretation it was established that the Olympic mascots are an expression of four strategies. In order of appearance they are as follows: demonstration of the localness of the nature of the host country of the Games; Global transparent strategies; Enigmatic strategies and demonstration of localness of the culture of the host country of the Games. Among the collected names of the mascots, it was found that they are the result of mnemotechnical procedures and demonstrate nominated or camouflaged locality. The analysis of the Olympic logotypes brought about a foreseeable outcome: all of them included the global symbol of the five Olympic rings. And the additional results (in order of occurrence) are as follows: The significant majority of the logotypes contain the name of the host city, several hold a symbol of a sport discipline, a few display a globally transparent stereotype - the colour of the season, some contain a picture in the colours of the Olympic rings..